Agricultural Tax - Condition and Prospects - Kisiel, Roman; Idźkowska, Katarzyna (Olsztyn Economic Journal, 2013)
During the recent years the issues of taxation on the family agricultural farms has been neglected frequently. Currently, with the discussions pending in Poland on the planned changes in that area, the issues of taxation imposed on agricultural farming requires a new approach. The main aim of this paper is to analyze the actual tax burden on farms in Poland and to investigate the impact of agricultural tax on the formation of revenue of local government. However, an important is to consult opinions of the farmers about the individual tax burden farming structures as well as the entire system of taxation. It is important also to propose changes in the tax applied to the Polish agriculture. Suggested by farmers alternatives in the taxation of individual farms can be used as an attempt to adjust the tax system in our country, to the solutions applied in EU member states. The paper presents the analysis of the taxation on family agricultural farms in Poland with particular focus on the agricultural tax. For the purpose of evaluating the actual burdens to the farms resulting from that title and the analysis of the volume of tax revenues to the budgets of selected communes in 2010, the method of secondary analysis of statistical data originating from the commune administration offices situated in the area of Mazowieckie voivodship was applied. It was analyzed the budgetary resolutions and reports on their implementation in the surveyed municipalities. The authors conducted the study using a questionnaire interview. The studies encompassing 200 family agricultural farms aimed at obtaining the opinions from farmers concerning the taxation system in Poland and possibilities of introducing changes proposed by the State.